Coupled‐inductor based diode assisted boost inverter for achieving highgain. Issue 3 (17th January 2019) - Iqbal, Taosif; Lu, Haibin; Zaman, Shah; Tan, Siew‐Chong; Li, Guojun; Zhang, Xiongwen
Abstract : A high‐gain single‐stage three‐phase coupled‐inductor diode‐assisted boost inverter (CL‐DABI) is presented for energy applications. A new scheme has been proposed which is simple, has less number of energy storage components and uses non‐shoot‐through pulse‐width modulation (PWM) techniques such as sine‐wave PWM and space vector modulation to get the maximum gain from a low‐voltage dc source. During simulation and hardware implementation, it was observed that the SPWM method resulted in a lower conversion rate and higher device stress. To improve the shortcomings, extended sine‐wave PWM (ESPWM) method is proposed to achieve high gain without compromising the conversion efficiency and putting devices under stress. Mathematical analysis, simulations results and experimental verifications are presented here. Hardware results prove the validity of the proposed CL‐DABI with ESPWM by achieving high intermediate dc gain, excellent dc–ac coupling, less device stress, comparable power quality and smaller size.